Analisis Pengaruh Kinerja Staf Operation terhadap Kepuasan Konsumen di Travel Agent Pacto Bali - Young, Michelle Klarissa; Nawangwulan, Wening Ramadhani Siti (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the influence of the quality of operations staff performance on consumer satisfaction at the Pacto Bali Travel Agent. The quality of operations staff performance is an important factor that can influence consumer satisfaction. The research method used in this research is descriptive research with a quantitative approach. This research has a sample population, namely guests who have used Pacto services using a sample of 98 respondents. This research technique uses data analysis techniques using simple linear regression. The results of this research state that the quality of operations staff performance has a significant influence on consumer satisfaction, which means that increasing the quality of operations staff performance can increase consumer satisfaction with Pacto Bali Travel Agents.